As desigualdades de acessibilidade às oportunidades cotidianas na Região Metropolitana de Belo Horizonte - Eugênia Viana Cerqueira; Alexandre Magno Alves Diniz (Confins)
This research provides a novel exploration of inequalities in accessibility to non-work urban opportunities in the Metropolitan Region of Belo Horizonte (RMBH). We combine the estimation of a cumulative opportunity accessibility indicator with the analysis of the population distribution to evaluate social and spatial disparities. Results outline that although low-income households have significantly lower accessibility to urban opportunities, the development of new suburban structures is followed by high accessibility levels in high-income neighborhoods. Findings depict two opposing segregation processes, where low-income groups are displaced to distant peripheral areas with low accessibility levels and high-income groups settle in low-density residential developments, but with high motorized accessibility to opportunities nearby. Moreover, results show that health facilities tend to be more concentrated in the urban core, yielding significant inequalities in accessibility.